2020
DOI: 10.3390/pathogens9110864
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Pathogenicity, and Mycotoxin Production of Fusarium temperatum in Relation to Other Fusarium Species on Maize in Germany

Abstract: Fusarium subglutinans is a plant pathogenic fungus infecting cereal grain crops. In 2011, the species was divided in Fusarium temperatumsp. nov. and F. subglutinans sensu stricto. In order to determine the occurrence and significance of F. temperatum and F. subglutinans on maize, a monitoring of maize ears and stalks was carried out in Germany in 2017 and 2018. Species identification was conducted by analysis of the translation elongation factor 1α (TEF-1α) gene. Ninety-four isolates of F. temperatum and eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…F. graminearum was detected in ≥ 80% of all Fusarium head blight (FHB) samples, sometimes even 100% 38 . In addition, the frequency of F. graminearum isolated from ears ranged from 30 to 71% with an average of 57%, and from stalks ranged from 43 to 81%, with the average of 65% 39 . Although the isolation frequency of F. graminearum from CFSR was only 3.65% in our present study, the potential risk of mycotoxins produced by F. graminearum to human health cannot be ignored 40 .…”
Section: Discussionmentioning
confidence: 99%
“…F. graminearum was detected in ≥ 80% of all Fusarium head blight (FHB) samples, sometimes even 100% 38 . In addition, the frequency of F. graminearum isolated from ears ranged from 30 to 71% with an average of 57%, and from stalks ranged from 43 to 81%, with the average of 65% 39 . Although the isolation frequency of F. graminearum from CFSR was only 3.65% in our present study, the potential risk of mycotoxins produced by F. graminearum to human health cannot be ignored 40 .…”
Section: Discussionmentioning
confidence: 99%
“…graminearum and F . verticillioides when isolated from naturally infected maize ears, with an even higher aggressiveness than the other two species (Pfordt, Schiwek, et al, 2020). Again, this example shows that we always have to be aware of Fusarium species shifts and that different Fusarium species colonize maize kernels at the same time (Reyes Gaige et al, 2020), including respective associated changes of mycotoxin profiles in maize kernels.…”
Section: Maize Ear Rots and Related Mycotoxin Productionmentioning
confidence: 99%
“…IMATHIU et al (2009) confirmed successful infection and disease development by all examined F. langsethiae isolates. According to PFORDT et al (2020) all observed isolates of F. temperatum and F. subglutinans affected winter wheat and caused moderate to severe FHB symptoms. OPOKU et al (2011) were assessing the aggressiveness of 20 different F. langsethiae isolates on wheat leaves by measuring the lesion length formerd at the inoculation site.…”
Section: Resultsmentioning
confidence: 99%